Design and methodology of the 'endometriosis and pelvic floor dysfunction' (EndoPFD) multicenter cross-sectional study - Eleonora Russo; Maria F. Brancalion; Tiziana Fidecicchi; Maria M. Montt-Guevara; Giulia Misasi; Clara Baroni; Riccardo Morganti; Cristina Zito; Elena Pisacreta; Sara Gorini; Alessandro Sturiale; Giorgio Pomara; et al. (Taylor & Francis Group, 2024)
Objective To assess the prevalence and the characteristics of pelvic floor dysfunction (PFD) in women with endometriosis.Methods This is a methodological paper that describes the 'Endometriosis and Pelvic Floor Dysfunction' (EndoPFD) multicenter study protocol. It involves three sites: the University Hospital of Pisa, the San Raffaele Hospital of Milan and the Vanvitelli University Hospital of Naples. Women are recruited through web links and are asked whether they want to participate to the clinical evaluation or only to the web survey. The web survey gathers personal history, endometriosis history and symptoms, and performs a subjective evaluation of PFD through questionnaires: Urinary Distress Inventory 6, Colorectal-Anal Distress Inventory 8, Wexner Scale for Fecal Incontinence, Wexner Constipation Scoring System, and Female Sexual Function Index. Those interested in the clinical evaluation will add to the questionnaires the following exams: gynecological and proctological exam, pelvic ultrasound, urodynamic test, and anorectal manometry.Preliminary results Recruitment for the web survey was completed. A total of 1,149 women signed the electronic consent, 329 were excluded due to inclusion/exclusion criteria; hence, 525 completed all the questionnaires (response rate of 64.02%). Recruitment for the clinical evaluation is ongoing.Discussion This study protocol offers the possibility to define the prevalence of PFD in endometriosis patients with a subjective and an objective assessment of signs and symptoms. This may pave the way for changing the approach to patients with endometriosis. Moreover, it demonstrates the validity of the method used (online survey and recruitment) to reach a high number of patients.